Converging practices: Fashion exhibits across museums and social media. Issue 1 (1st June 2019) - Jenss, Heike
The term 'curation' has migrated from the museum into everyday life, particularly on social media, and this speaks to a shifting understanding of people's engagement with arts, culture and commodities. 'Curation' accentuates the participatory nature of social media, as users co-produce, edit and share content online. The term also alludes to social media's capacity as archive and exhibition space for the documentation, display, collection and recollection of looks and styles, experiences, events and emotions. The Costume Institute at the Metropolitan Museum of Art (MET) in New York was one of the first museums to acknowledge the increasing impact of participatory media with the 2007 exhibition blog.mode: addressing fashion. This established a connection between the museum collection and the fashion blog as two different forms of fashion archiving, display and discourse. Today, the use of social media and the museum visitor's own image production (for example, for #artselfies) is a component of curatorial practice, increasing the appeal of fashion exhibitions and new forms of engagement with museums and museum objects.By reviewing selected examples of fashion museums and archives in the United States – two major museums and two independent online archives – this article explores some of the convergences between the material culture of fashion, mediatization and musealization, including fashion curation beyond the museum, and cultural memory-making through ephemeral media.